Oral Therapy Extension Programme (OTEP): phase II, (Oct.1983-September 1986) - BRAC (© BRAC, 2016)
1. Introduction 2. Background of oral therapy 3. Working strategy and methodology 4. New concepts and strategies 5. Operational achievements 6. Publicity 7. Training and recruitment 8. Personnel 9. Usage survey